The influence of corporate characteristics on CSR reporting in Serbia - Markovic, Ivana; Janković Perić, Marina; Rabasović, Biljana (Serbian Journal of Management, 2024)
The trend that increasingly places importance on environmental protection, ethical behavior towards all relevant stakeholders, and community involvement puts the business practices of large companies and the consequences that business has on society as a whole under the public’s supervision. For this reason, corporate social responsibility disclosures are constantly gaining importance and attracting the attention of the professional and academic public. The aim of the study is to examine the influence of corporate characteristics (ownership structure, age, and size) on CSR reporting on a sample of corporations whose shares are listed on the Belgrade Stock Exchange in the regulated part of the market in the time period from 2017 to 2021. Panel regression analysis was used to test the hypotheses. The results of the survey indicate that the concentration of ownership and the age of corporations have a statistically significant negative impact, while the size of the corporation has a statistically significant positive impact on reporting on corporate social responsibility in the Republic of Serbia.
Keywords: CSR reporting; CSR disclosures; ownership structure; size; age